Kethoprak Reog Paguyuban Seni Reog Singo Bhirowo Lakon Suminten Edan (Kolaborasi Kesenian Rakyat sebagai Ekspresi Akulturasi Budaya) - Dipoyono, Achmad; Imama, Yulela Nur (Institut Seni Indoensia Surakarta, 2023)
ABSTRACT The city of Surakarta has approximately 35 groups or communities dedicated to the Reog art form. One of these groups is known as